2019
DOI: 10.1371/journal.pone.0224458
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellum-mediated trainability of eye and head movements for dynamic gazing

Abstract: ObjectiveTo investigate whether gaze stabilization exercises (GSEs) improve eye and head movements and whether low-frequency cerebellar repetitive transcranial magnetic stimulation (rTMS) inhibits GSE trainability.Methods25 healthy adults (real rTMS, n = 12; sham rTMS, n = 13) were recruited. Real or sham rTMS was performed for 15 min (1 Hz, 900 stimulations). The center of the butterfly coil was set 1 cm below the inion in the real rTMS. Following stimulation, 10 trials of 1 min of a GSE were conducted at 1 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…The participants were instructed to lie down on a bed in the prone position. Because previous studies have shown that the figure-of-eight coil could stimulate the cerebellum (Haarmeier and Kammer, 2010;Popa et al, 2010;Tremblay et al, 2016), a magnetic stimulator (MagPro compact, MagVenture, Denmark) was used to deliver TMS to the cerebellum with a butterfly coil (MC-B70, MagVenture, Denmark) (Matsugi et al, 2019). The center of the coil's junction was set at a distance 1 cm below the inion to stimulate the central region of the cerebellum (Zangemeister and Nagel, 2001;Nagel and Zangemeister, 2003;Jayasekeran et al, 2011;Hardwick et al, 2014;van Dun et al, 2017); prior research has demonstrated that stimulation from this position can modulate vestibular and ocular motor functions (Zangemeister and Nagel, 2001;Nagel and Zangemeister, 2003;Jenkinson and Miall, 2010).…”
Section: Cerebellar Repetitive Tms (Crtms)mentioning
confidence: 99%
See 3 more Smart Citations
“…The participants were instructed to lie down on a bed in the prone position. Because previous studies have shown that the figure-of-eight coil could stimulate the cerebellum (Haarmeier and Kammer, 2010;Popa et al, 2010;Tremblay et al, 2016), a magnetic stimulator (MagPro compact, MagVenture, Denmark) was used to deliver TMS to the cerebellum with a butterfly coil (MC-B70, MagVenture, Denmark) (Matsugi et al, 2019). The center of the coil's junction was set at a distance 1 cm below the inion to stimulate the central region of the cerebellum (Zangemeister and Nagel, 2001;Nagel and Zangemeister, 2003;Jayasekeran et al, 2011;Hardwick et al, 2014;van Dun et al, 2017); prior research has demonstrated that stimulation from this position can modulate vestibular and ocular motor functions (Zangemeister and Nagel, 2001;Nagel and Zangemeister, 2003;Jenkinson and Miall, 2010).…”
Section: Cerebellar Repetitive Tms (Crtms)mentioning
confidence: 99%
“…As previous studies have observed that an upward current applied to the cerebellum can effectively stimulate this region (Ugawa et al, 1995;Hiraoka et al, 2010;Matsugi et al, 2013), the coil was oriented such that the current therein was directed downward to deliver the upward current to the brain (van Dun et al, 2017). TMS intensity was set to 50% of the maximum stimulator output: the same setting as those employed by previous studies investigating cerebellar and vestibular functions (Zangemeister and Nagel, 2001; Nagel and Zangemeister, 2003;Haarmeier and Kammer, 2010;Jenkinson and Miall, 2010;van Dun et al, 2017;Matsugi et al, 2019). Because a 1-Hz crTMS reduces motor function and motor adaptation (Miall and Christensen, 2004;Jenkinson and Miall, 2010) the inter-stimulus interval was set at 1 s, and 900 pulses were applied (Fierro et al, 2007;Popa et al, 2010;Matsugi et al, 2019).…”
Section: Cerebellar Repetitive Tms (Crtms)mentioning
confidence: 99%
See 2 more Smart Citations
“…Transcranial magnetic stimulation (TMS) is often used for assessing motor control associated with the primary motor cortex (M1) [1]. Repetitive [2,3], paired-pulse [4], and single-pulse TMS enables the probing of neural circuit function in M1 [1]. Single-pulse TMS induces a silent period (SP) on electromyography (EMG) in hand muscles during the slight voluntary muscle contraction that follows motor-evoked potentials (MEPs) [5,6].…”
Section: Introductionmentioning
confidence: 99%